On Beneficiaries’ Inscriptions from the South of the Province of Dalmatia (A few examples from the area of east Herzegovina) - Samardžić, Gligor M (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
The paper presents data on consular beneficiaries’ stations in the area of east Herzegovina (the south of the province of Dalmatia). It addresses the beneficiaries’ sacrificial votaries from the municipium Diluntum situated on the Aquileia–Dyrrachium main road. Legionaries legio XIV Gemina and legio I Italica served as consular beneficiaries in the previously mentioned area. The paper also presents comprehensive critical insight with particular reference to the function and position of consular beneficiaries who were keepers of public security during the Principate and later.
Keywords: east Herzegovina; Dalmatia; Diluntum; legions; beneficiaries